Smart regulations in maritime governance: Efficacy, gaps, and stakeholder perspectives - Olaniyi, Eunice O. (Elsevier Ltd, 2025)
The paper explores maritime environmental regulations, analyzing industry perspectives and their operational execution. It critically assesses the International Maritime Organization (IMO) regulations' effectiveness in mitigating climate challenges within the shipping domain. The central argument is that the evolving and intricate nature of maritime regulations often impedes policy goal realization, enforcement, impact evaluation, and equity perception. Utilizing both quantitative and qualitative methodologies, this research gathers, analyses, and interprets data via surveys and interviews. This exploration seeks to evaluate the regulations' impact on reducing shipping's negative impact, especially concerning emissions, waste management, and noise pollution, under the umbrella of smart regulations. The results indicate that the current regulatory approach is neither comprehensive nor immediate, necessitating a more agile, digitally enabled framework to adapt to fast-changing industry conditions.